2008
DOI: 10.1248/jhs.54.686
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Enterotoxic Hemolysin in Pathogenicity of Vibrio mimicus

Abstract: Vibrio mimicus (V. mimicus) is a causative agent of human gastroenteritis and food poisoning. Although several toxic or virulence factors have been isolated from the bacterium, an enterotoxic hemolysin is a sole toxin produced by all clinical isolates. In the present study, we found that the antibody against the hemolysin significantly inhibited the fluidaccumulating action of the living cells inoculated into a rabbit ileal loop, and that the hemolysin gene (vmhA) was probably expressed by the bacterium in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Previous studies showed that the T3SSs of V. parahaemolyticus and V. cholerae contribute to their pathogenicity for humans [ 14 , 17 , 20 , 22 - 24 ]. In V. mimicus , a bacterium which is known to be a causative agent of gastroenteritis in humans, the hemolysin was previously reported as a major virulence factor [ 26 ]. To assess the function of T3SS of V. mimicus in pathogenicity in our study, we evaluated the cytotoxicity of V. mimicus for Caco-2 cells because V. parahaemolyticus had a T3SS2-dependent cytotoxic effect on Caco-2 cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the T3SSs of V. parahaemolyticus and V. cholerae contribute to their pathogenicity for humans [ 14 , 17 , 20 , 22 - 24 ]. In V. mimicus , a bacterium which is known to be a causative agent of gastroenteritis in humans, the hemolysin was previously reported as a major virulence factor [ 26 ]. To assess the function of T3SS of V. mimicus in pathogenicity in our study, we evaluated the cytotoxicity of V. mimicus for Caco-2 cells because V. parahaemolyticus had a T3SS2-dependent cytotoxic effect on Caco-2 cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not detect statistically significant differences between T3SS-deficient mutants and parental strains, there was a tendency for the cytotoxicity of T3SS-deficient mutants to diminish than that of the parental mutants. A previous report showed that the deletion of the hemolysin gene in V. mimicus significantly reduced fluid accumulation in rabbit ileal loop tests, but the mutant partially retained this action, which suggests that, besides the hemolysin, V. mimicus may contain an additional virulence determinant(s) [ 26 ]. It is therefore possible that T3SS is a candidate for the previously unidentified virulence determinant in pathogenic V. mimicus strains for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although several enterotoxic factors, including a cholera toxin鈥恖ike enterotoxin, have been isolated [4,5], a heat鈥恖abile hemolysin, designated V. mimicus hemolysin (VMH) [6], may be the most important virulence factor of the pathogen. Purified VMH can induce fluid accumulation when injected into a ligated ileal loop [6,7] and specific antibody against VMH significantly inhibits fluid accumulation [6,8]. A VMH鈥恘egative mutant showed reduced ability to cause fluid accumulation [8].…”
mentioning
confidence: 99%
“…Purified VMH can induce fluid accumulation when injected into a ligated ileal loop [6,7] and specific antibody against VMH significantly inhibits fluid accumulation [6,8]. A VMH鈥恘egative mutant showed reduced ability to cause fluid accumulation [8]. Moreover, the gene encoding VMH is present in all strains from various clinical and environmental sources [9].…”
mentioning
confidence: 99%
“…Therefore, although the hemolytic activity of VMH is apparently reduced, the enterotoxic activity may be not eliminated by incubation with HD-5. VMH has been documented to be a determinant of the putative virulence of diarrheal diseases Miyoshi t al., 1997;Li et al, 2008 . The findings shown herein may support the FIG.…”
Section: Figmentioning
confidence: 99%